Implementasi Algoritma DES (Data Encryption Standard) Pada Enkripsi Dan Deskripsi SMS Berbasis Android - Deny Adhar (JTIK (Jurnal Teknik Informatika Kaputama), 2019)
The development of technology makes the birth of a tool that is the forerunner to the formation of Short Messaging Service (SMS), namely pagers. However, with the community's need to send messages quickly, accurately and safely make technology experts create a device that is a cellphone. Cellphone or mobile was first created already equipped with SMS feature. When a message or data becomes important and is privacy, it is necessary to protect the data. Therefore experts created an algorithm method to secure data. This method is called the encryption and decryption method to secure highly confidential messages or information from irresponsible and unauthorized people. There are various kinds of encryption algorithms with each characteristic that can be used, one of which is the DES (Data Enryption Standard) algorithm. DES is a symmetric encryption algorithm, where the process of encrypting and decrypting messages uses the same key. So even though a cryptografe understands the algorithm used to encode the message, but if you don't know the key used, it won't be able to decrypt the message so that the SMS message is really safe. Keywords: SMS, Cryptography, Enkripsi, Dekripsi, DES Algorithm